2007
DOI: 10.3892/or.18.1.77
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase inhibitors suppress the growth of leukemia and lymphoma cells

Abstract: Abstract. γ-Secretase inhibitors (GSI) suppress the growth of acute T-lymphoblastic leukemia (T-ALL) cells with NOTCH1 mutations. Recently, clinical trials of GSI for refractory T-ALL have commenced. In the present study, we examined the effects of three types of GSI; GSI-I, GSI-IX, and GSI-XII on the growth of four B-cell malignant lymphoma (B-ML) and four acute myeloid leukemia (AML) cell lines as well as four T-ALL cell lines. We found that GSI also suppressed the in vitro growth of some B-ML and AML cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…on May 9, 2018. by guest www.bloodjournal.org From but it has been shown that ␥-secretase inhibitors may be useful for the treatment of hematologic malignancies other than T-ALL. 46 Although the mechanism behind the cytotoxic effects of ␥-secretase inhibitors remains to be clarified, it has been proposed that Notch1 signaling confers chemoresistance by inhibiting p53 pathway through mTOR-dependent PI3K-Akt/ PKB pathway. 41 In considering the potential cytotoxic activity of the combination of Nutlin-3 plus ␥-secretase inhibitors toward normal tissues, previous studies have shown that Nutlin-3 is much less toxic against normal tissues with respect to neoplastic cells, 2 and might even protect normal cells from apoptosis induced by mitotic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…on May 9, 2018. by guest www.bloodjournal.org From but it has been shown that ␥-secretase inhibitors may be useful for the treatment of hematologic malignancies other than T-ALL. 46 Although the mechanism behind the cytotoxic effects of ␥-secretase inhibitors remains to be clarified, it has been proposed that Notch1 signaling confers chemoresistance by inhibiting p53 pathway through mTOR-dependent PI3K-Akt/ PKB pathway. 41 In considering the potential cytotoxic activity of the combination of Nutlin-3 plus ␥-secretase inhibitors toward normal tissues, previous studies have shown that Nutlin-3 is much less toxic against normal tissues with respect to neoplastic cells, 2 and might even protect normal cells from apoptosis induced by mitotic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…When EBNA2-ER is activated in P493-6 cells by estradiol, EBNA2 direct activation of Notch target genes would not require ligand-activated Notch, and hence EBNA2-ER-driven P493-6 cells would be resistant to γ-secretase inhibitors, as we have documented. A recent study reports that selected B-cell lines are sensitive to the GSIs, suggesting a therapeutic role for GSIs in B lymphoid malignancies (20). Interestingly, Jagged2 levels are increased in samples from multiple myeloma patients (8), which often have Myc overexpression (8,11).…”
Section: High Myc State Increases Notch Signaling Components With Jagmentioning
confidence: 99%
“…These findings suggest that JAG2 is necessary for maximal P493-6 cell proliferation in vitro. Previous studies have shown that inhibition of the γ-secretase Presenillin-1 reduces the production of the Notch intracellular domain, and subsequent downstream signaling, often resulting in apoptosis (20). To further study JAG2 loss-of-function in vitro and in vivo, we used the γ-secretase inhibitor (GSI) DAPT, which blocks Notch signaling by preventing the processing of the Notch1 receptor to form N ICD , but not the levels of Myc expression.…”
Section: High Myc State Increases Notch Signaling Components With Jagmentioning
confidence: 99%
“…Cells were treated with 7.5 μmol/L LLNle or DAPT or vehicle alone (DMSO 0.1%), unless otherwise indicated, and kept in a humidified 5% CO 2 atmosphere at 37°C for the indicated time period. This concentration is in the low range reported by several previous in vitro studies (38,(74)(75)(76)(77). The γ-secretase inhibitor L-685,458 and the proteasome inhibitor lactacystin were obtained from SigmaAldrich, dissolved at 10 mmol/L in DMSO and 30 mmol/L in H 2 O, respectively, aliquoted, and stored in the dark at −20°C.…”
Section: Cell Culturementioning
confidence: 99%